Climate Change Impacts on Biodiversity - Coristine, Laura Elizabeth (Université d'Ottawa / University of Ottawa, 2016)
Conservation is plagued by the issue of prioritization - what to conserve and where to conserve it - which relies on identification and assessment of risks. In this body of work, I identify some of the risks related to climate change impacts on biodiversity, as well as potential solutions. Climate changes are underway across nearly all terrestrial areas and will continue in response to greenhouse gas emissions over centuries. Other extinction drivers, such as habitat loss due to urbanization, commonly operate over localized areas. Urbanization contributes, at most, less than 2% of the total range loss for terrestrial species at risk when averaged within an ecodistrict (Chapter 2). Documented impacts of climate change, to date, include: extinction, population loss, reduction in range area, and decreased abundance for multiple taxonomic groups. Examining species’ and populations’ physiological limits provides insight into the mechanistic basis, as well as geography, of climate change impacts (Chapter 3). Climate changes, and the ecological impacts of climate changes, are scale-dependent. Thus, the biotic implications are more accurately assessed through comparisons of local impacts for populations. Under a scenario of climate change, equatorward margins may be strongly limited by climatic conditions and not by biotic interactions. Yet, geographic responses at poleward margins do not appear directly linked to changes in breeding season temperature (Chapter 4). New ideas on how regions with attenuated climate change (climate refugia) may be used to lower species climate-related extinction risk while simultaneously improving habitat connectivity should be considered in the context of potential future consequences (i.e. range disjunction, alternative biological responses) (Chapter 5). Contemporary climate refugia are identifiable along multiple climatic dimensions, and are similar in size to current protected areas (Chapter 6). Determining how, when, and where species distributions are displaced by climate change as well as methods of reducing climatic displacement involves integrating knowledge from distribution shift rates for populations, occurrence of climate refugia, and dispersal barriers. Such assessments, in the Yellowstone to Yukon region, identify dramatically different pathways for connectivity than assessments that are not informed by considerations of species richness and mobility (Chapter 7).
Keywords: climate change; habitat loss; climate refugia; policy; conservation; physiological tolerance; range margin; connectivity